Money and macrodynamics : Alfred Eichner and post-Keynesian economics - Lavoie, M. (Marc); Rochon, Louis-Philippe; Seccareccia, Mario (M.E. Sharpe, 2010)
Alfred Eichner's pioneering contributions to post-Keynesian economics offered significant insights on the way modern economies and institutions actually work. Featuring chapters by many of Eichner's disciples, this book celebrates his rich contributions to post-Keynesian economics and demonstrates that in many ways his work is as valid today as it was over two decades ago.